2022
DOI: 10.5664/jcsm.10170
|View full text |Cite
|
Sign up to set email alerts
|

Sleep reactivity predicts insomnia in patients diagnosed with breast cancer

Abstract: Study objectives: To examine the role of sleep reactivity as a predictor of insomnia in patients diagnosed with breast cancer.Methods: One hundred and seventy three women with breast cancer participated and were followed up over a period of 9 months. At baseline participants were assigned to a high (n=114) or low (n=59) sleep reactivity group, based on their responses to the Ford Insomnia Response to Stress Test (FIRST). We assessed whether these FIRST groupings (high / low sleep reactivity) predicted changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Ultimately, this study reveals that even normal sleepers with high sleep reactivity experience a considerable worsening of their sleep during cancer care and, more importantly, that the FIRST can identify patients at‐risk of insomnia disorder prior to this foreseeable precipitant (Rehman et al, 2022). This suggests the FIRST may be useful for detecting individuals most in need of preventive insomnia treatment before they encounter predictable stressors (e.g., new emergency responders prior to first‐time emergency work) (Reffi & Cheng, 2023).…”
Section: Sleep Reactivity As a Predisposition To Insomniamentioning
confidence: 96%
See 2 more Smart Citations
“…Ultimately, this study reveals that even normal sleepers with high sleep reactivity experience a considerable worsening of their sleep during cancer care and, more importantly, that the FIRST can identify patients at‐risk of insomnia disorder prior to this foreseeable precipitant (Rehman et al, 2022). This suggests the FIRST may be useful for detecting individuals most in need of preventive insomnia treatment before they encounter predictable stressors (e.g., new emergency responders prior to first‐time emergency work) (Reffi & Cheng, 2023).…”
Section: Sleep Reactivity As a Predisposition To Insomniamentioning
confidence: 96%
“…A team in Scotland built on this enterprise of early risk detection among women diagnosed with non‐metastatic breast cancer ( N = 173, mean age 58 years) (Rehman et al, 2022), a population beset by high rates of unremitting insomnia (Fleming et al, 2019; Savard et al, 2011). All women had a prognosis of >6 months and enrolled shortly following their diagnosis but prior to beginning cancer treatment.…”
Section: Sleep Reactivity As a Predisposition To Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…A total score above 14 indicates clinical insomnia. [22][23][24][25][26][27][28] Boysan et al found a sufficient internal consistency coefficient (Cronbach's α = 0.79) of the Turkish version of the ISI. 35 We found robust internal consistency (Cronbach's α = 0.80) in our study.…”
Section: Insomnia Severity Indexmentioning
confidence: 99%
“…27 Sleep reactivity using the FIRST has also been validated as a predictor of insomnia following a cancer diagnosis. 28 In light of the above findings, the FIRST may help as a tool to predict development of insomnia after various types of stress exposures.…”
Section: Introductionmentioning
confidence: 97%